2005
DOI: 10.1242/dev.01609
|View full text |Cite
|
Sign up to set email alerts
|

Label-retaining epithelial cells in mouse mammary gland divide asymmetrically and retain their template DNA strands

Abstract: It has been postulated that the stem cells of somatic tissues protect themselves from mutation and cancer risk by selective segregation of their template DNA strands. Self-renewing mammary epithelial stem cells that were originated during allometric growth of the mammary ducts in pubertal females were labeled using [3H]-thymidine (3HTdR). After a prolonged chase during which much of the branching duct morphogenesis was completed, 3HTdR-label retaining epithelial cells (LREC) were detected among the epithelium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
236
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 266 publications
(252 citation statements)
references
References 20 publications
11
236
0
5
Order By: Relevance
“…It was proposed that stem cells might always inherit template-containing DNA strands allowing them to escape cancer-causing mutations. In support of the genome-wide directedsegregation mechanism, nonrandom segregation of sister chromatids was observed in some studies that followed the distribution of bromo-deoxyuridine-or radio-labeled chromosomes (Lark et al 1966;Rosenberger and Kessel 1968;Potten et al 1978;Merok et al 2002;Smith 2005), while the random pattern was found in other studies (Ito and McGhee 1987;Yadlapalli et al 2011). Another interesting case of selective segregation of chromatids of only the paternal set of chromosomes in the apical cells of shoots and roots of the water fern Marsilea vestita has been reported (Tourte et al 1980).…”
Section: Discussionmentioning
confidence: 93%
“…It was proposed that stem cells might always inherit template-containing DNA strands allowing them to escape cancer-causing mutations. In support of the genome-wide directedsegregation mechanism, nonrandom segregation of sister chromatids was observed in some studies that followed the distribution of bromo-deoxyuridine-or radio-labeled chromosomes (Lark et al 1966;Rosenberger and Kessel 1968;Potten et al 1978;Merok et al 2002;Smith 2005), while the random pattern was found in other studies (Ito and McGhee 1987;Yadlapalli et al 2011). Another interesting case of selective segregation of chromatids of only the paternal set of chromosomes in the apical cells of shoots and roots of the water fern Marsilea vestita has been reported (Tourte et al 1980).…”
Section: Discussionmentioning
confidence: 93%
“…By performing pulse-chase experiments with DNA labels, Smith et al showed there was a population of cells within the mammary gland which retained their DNA label through asymmetric segregation of DNA strands. These cells were still actively dividing and featured stem cell characteristics [14]. Roughly 30-40% of the cells that retained their DNA label also expressed receptors for the reproductive hormones estrogen and progesterone [15].…”
Section: Identification Of Mascsmentioning
confidence: 99%
“…Thus, any errors in replication are readily transferred (within one generation) to TACs that are soon lost from the population. Such a mechanism will produce LRCs after injection of DNA labels when stem cells are being formed, but validation of the hypothesis requires the observation that LRCs go through further rounds of DNA synthesis, yet still segregating the immortal DNA strands from sister chromatids into the daughter cells that remain as stem cells; this has been demonstrated in the small intestine and breast [9,10], and in some muscle satellite cells [11]. The existence of LRCs during normal stem cell renewal is based upon the random segregation of sister chromatids; however, this is somewhat incompatible with the 'immortal strand hypothesis', which predicts loss of a newly incorporated DNA synthesis marker within two cycles [12].…”
Section: Selective Dna Strand Segregationmentioning
confidence: 99%